Impact of Climate Change on Dengue Haemorrhagic Fever in Central Java. - Setiani, Onny (Jurnal Kesehatan Lingkungan Indonesia, 2003)
ABSTRACT Background: Dengue viruses, single stranded RNA viruses of the family flaviridae is increasing global concern in public  health. They cause an estimated 50-100 million illnesses annually  around the world  This disease often show regular seasonal patterns in incidence because of the sensitivity of mosquito vectors to climate change. The objectives of this study are to study the vulnerability, assessment and adaptation measures  of Dengue Haemorrhagic  Fever (DHF)  incidence in  Central Java. Methods: Twenty eight Districts in Central Java were  selected for analysis of meteorological parameters and incidence of DHF from predictive value point of few. Annual time series analysis of data on temperature, humidity, rainfall, dengue fever incidence for a period of year 2000 until 2002  including the period of outbreak dengue were analyzed. Results: The finding illustrate that DHF incidence has significant moderate positive correlation  with air temperature and moderate negative correlation with total rain fall and relative humidity. The incidence of DHF in more likely consistent to temperature pattern than rain fall or humidity. Climate warming, expressed as a systematic temperature increase in most areas seems to be responsible for an increase of DHF incidence. Conclusions: It is  suggested  that rain fall, humidity and temperature may be used for prediction of  DHF  incidence.   Keywords: Climate change, Dengue Haemorrhagic Fever (DHF), Central Java